What Survival Strategies for Sub-Saharan Migrant Woman? Networking Competences in a Gender-Aware Perspective - Giovanna Campani; Zoran Lapov (Firenze University Press, 2015)
e paper focuses on the European LeFamSol Project dedicated to women native to Sub-Saharan Africa. Following its objectives, the Project has developed several practice-oriented pedagogical actions relying on survival strategies, and networking competences coupled with gender awareness.  e core idea is to train female African migrants to become "resource persons" for newcomers in order to help them in mobilising their survival strategies in South Europe by facilitating the circulation of information and knowledge on national and transnational levels.  is strategic pro le is being materialised in "network facilitator", a professional  gure that brings together the tasks of informant, mediator, guide, adviser, interpreter, along with other relevant skills, to be put into practice within activity of network facilitating.